Echo Sounding of Frozen Lake from Surface of Ice - Hashimoto, Tomiju; Maniwa, Yoshinobu; Omoto, Osamu; Noda, Hidekuni (The International Hydrographic Review, 2015)
In this paper the authors give the result of their research carried out on the echo sounding of a frozen lake. The echo trace of the lake bottom was obtained from the ice surface. It is obviously easy to determine accurately the positions of soundings from that surface. Therefore, soundings were carried out more rapidly and accurately on the surface of the ice than they would have been from a boat. Furthermore, the detection of schools of fish from the ice surface was successful for the first time, and the transmission loss of ultrasonic waves in artificial ice and in natural ice was also measured.